Building the Field of Health Policy and Systems Research: Social Science Matters - Gilson, Lucy; Hanson, Kara; Sheikh, Kabir; Akua Agyepong, Irene; Ssengooba, Freddie; Bennett, Sara (PLoS medicine, 2011)
The first paper in this series on building mthe field of Health Policy and Systems Research (HPSR) in low- and middle income countries (LMICs) [1] outlined the scope and questions of the field and highlighted the key challenges and opportunities it is currently facing. This paper examines more closely one key challenge, the risk of disciplinary capture the imposition of a particular knowledge frame on the field, privileging some questions and methodologies above others. In HPSR the risk of disciplinary capture can be seen in the current methodological critique of the field, with consequences for its status and development (especially when expressed by research leaders). The main criticisms are reported to be: that the context specificity of the research makes generalisation from its findings difficult; lack of sufficiently clear conclusions for policy makers; and questionable quality and rigour [2].
Keywords: Field of Health Policy; Systems Research; Social Science Matters